Alla scoperta dei casi estremi di plurilinguismo individuale: le traiettorie di alcuni iperpoliglotti in prospettiva sociolinguistica - Murrmann, Julia (Neophilologica, 2017)
Independently of how we decide to define plurilinguilism and how many languages should a person identified as a hyperpolyglot speak, the potentially unlimited individual’s capacity to express in many languages is one of the most striking features of the human species. Indeed, homo sapiens is multilingual by nature: the linguistic repertoire of a speaker is vast and each individual, at least theoretically, has at one’s disposal unlimited possibilities to shape own expressive resources. In practice, while some struggle to learn a foreign language, the others learn many languages competently and effortlessly. Moreover, some have succeeded in mastering multiple, say ten or more, foreign languages. Numerous theories exist as explanations for polyglotism, including the innate or acquired individual mental capacities, cultural background and specific social circumstances. The objective of the paper is to trace life trajectories of a few eminent hyperpolyglots who became fluent in multiple languages.